2006
DOI: 10.1007/s11883-006-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardioembolic stroke

Abstract: Cardiac sources of emboli account for over one quarter of all ischemic strokes. Strokes due to cardioembolism are in general severe and prone to early and long-term recurrence. Nonvalvular atrial fibrillation remains the most common cause of cardioembolic stroke. Despite the proven efficacy of oral anticoagulation, it is prescribed for less than half of the patients with risk factors for embolism and no contraindications for anticoagulation. The embolic risk of patent foramen ovale is low except when combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 54 publications
2
68
0
6
Order By: Relevance
“…Cardioembolic strokes usually have more severe clinical status and a higher risk of recurrence in the short term compared to other stroke groups (13,14). Echocardiography serves as the cornerstone in evaluating patients who may have had a cardioembolic stroke (15).…”
Section: Discussionmentioning
confidence: 99%
“…Cardioembolic strokes usually have more severe clinical status and a higher risk of recurrence in the short term compared to other stroke groups (13,14). Echocardiography serves as the cornerstone in evaluating patients who may have had a cardioembolic stroke (15).…”
Section: Discussionmentioning
confidence: 99%
“…25,26,28,29 Moreover, CES is generally severe, reflected by greater disability, greater rates of stroke recurrence, and greater mortality than in other subtypes of strokes. 24,30 Prior knowledge of a diagnosis of AF and appropriate anticoagulation is therefore important to reduce the risk for stroke in such patients. Clinical trials on stroke prevention in patients with AF have shown that anticoagulation with warfarin reduces the risk for stroke substantially 25,31 and is more effective than therapy with antiplatelet agents such as aspirin and clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is associated with at least a fivefold increased incidence of stroke [34], with embolism of cardiac origin accounting for over one-fifth of all ischemic strokes [3,19]. The incidence of first-ever cardioembolic stroke is estimated to be 30 per 100,000 population [15], Stroke due to cardioembolism is also associated with a higher mortality and carries the risk of early and long-term recurrence [9,10]; consequently, it is a significant health-care challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology and clinical features of cardioembolic stoke have been investigated in several studies [3,10,15,19]. Health-economic evaluations, however, on this important clinical condition are scarce.…”
Section: Introductionmentioning
confidence: 99%